2008
DOI: 10.1002/ajmg.a.32248
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cytogenetic characterization of a unique and complex de novo 8p rearrangement

Abstract: Human chromosome 8p is prone to recurrent rearrangements with inv dup del(8p) being most common. Each of these recurrent rearrangements is associated with different clinical manifestations. Some of these recurrent rearrangements at 8p are mediated by an 8p submicroscopic paracentric inversion between the olfactory gene clusters present in one of the parents. However, recent reports have shown that some of the rearrangements are unique and complex and are mediated by other repetitive elements within 8p. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…Despite the high frequency of inversion heterozygotes, the prevalence of the recurrent inverted, duplicated, and deleted 8p has been estimated at only one in 20,000; thus, in the absence of any evidence for a high rate of in utero fetal loss, the predisposition is relatively weak given the high frequency of the common inversion. In addition, ectopic recombination may not be the exclusive mechanism, as non-homologous end joining (NHEJ) has been invoked in a case in which neither parent carried the heterozygous inversion (Cooke et al 2008).…”
Section: Predisposition To Large-scale Imbalances Of 8pmentioning
confidence: 99%
“…Despite the high frequency of inversion heterozygotes, the prevalence of the recurrent inverted, duplicated, and deleted 8p has been estimated at only one in 20,000; thus, in the absence of any evidence for a high rate of in utero fetal loss, the predisposition is relatively weak given the high frequency of the common inversion. In addition, ectopic recombination may not be the exclusive mechanism, as non-homologous end joining (NHEJ) has been invoked in a case in which neither parent carried the heterozygous inversion (Cooke et al 2008).…”
Section: Predisposition To Large-scale Imbalances Of 8pmentioning
confidence: 99%
“…In addition, the proximal breakpoint of the duplication in reported case 4 appeared to map to this region (Table 2). 5 The NRG1 gene was disrupted in two of the ten abnormal patients (patients 7 and 9) in this study. Breakpoints of genomic rearrangements occurring in the NRG1 gene were observed in other reported cases with 8p genomic abnormalities, 49,50 indicating that unknown genomic structural features within the NRG1 gene may be susceptible to these various genomic rearrangements.…”
Section: P231 Duplicationmentioning
confidence: 65%
“…[2][3][4][5][6] These REPD-and/or REPP-related 8p genomic rearrangements include (1) the 8p23.1 deletion or duplication between REPD and REPP, [6][7][8][9] (2) the 8p23.1 paracentric inversion between REPD and REPP, 8,10 (3) the pericentric inversion (inv(8)(p23.1q22.1)) and recombinant chromosome 8 (rec (8)dup(8q)inv(8)(p23.1q22.1)), 11 (4) the 8p interstitial inverted duplication with associated terminal deletion (inv dup del(8p)), 5,6,8,10,[12][13][14][15][16][17][18][19][20][21][22][23][24] (5) the 8p translocations involving the 8p23.1, 25,26 and (6) different types of supernumerary chromosome 8 (SMC (8)) involving the breakpoints within 8p23.1. 4,27 In addition to these defined 8p genomic abnormalities, other pathogenic genomic changes have been identified, [28][29][30] whereas numerous genomic imbalances on 8p are still described as copy number variants (CNVs) of unknown clinical significance or CNVs without apparent clinical significance (benign CNVs) (http://projects.tcag.ca/variation).…”
Section: Introductionmentioning
confidence: 99%
“…Although the Utype exchange (mechanism 3) is the most frequent inv dup del mechanism in all other chromosome arms [Rowe et al, 2009], the majority of reported inv dup del(8p) can be explained by the mechanisms 1 or 2 mentioned above ( fig. 4 ; table 3 ) [Weleber et al, 1976;Dill et al, 1987;Minelli et al, 1993;Barber et al, 1994;de Die-Smulders et al, 1995;Guo et al, 1995;Floridia et al, 1996;Macmillin et al, 2000;Giglio et al, 2001;Pabst et al, 2003;Felbor et al, 2004;Shimokawa et al, 2004Shimokawa et al, , 2005Cooke et al, 2008;Zuffardi et al, 2009] with few exceptions [Buysse et al, 2009;Rowe et al, 2009]. In this study, the formation of the inv dup del(8p) appears to be caused by mechanism 2 in patient 2, and by mechanism 3 in patient 3 ( fig.…”
Section: Discussionmentioning
confidence: 78%